2009
DOI: 10.1177/1094428109334368
|View full text |Cite
|
Sign up to set email alerts
|

Are We There Yet?

Abstract: Research design is a central element of empirical research, and thus, an important consideration for entrepreneurship researchers and anyone interested in entrepreneurship-related research findings. Yet, many years have past since the last thorough review of research design and construct measurement practices. Thus, it is unknown whether there is a gap between what is currently being done versus what needs to be done. In this article, authors use a two-study approach involving a content analysis of published e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 23 publications
0
13
1
1
Order By: Relevance
“…Content analysis was used to identify the distribution of research strategies and techniques reported in the selected journals. Content analysis has been utilised to determine the extent to which scholars used mixed methods research (Bryman 2005;Crook et al, 2009;Greene, Caracelli & Graham 1989;Leech & Onwuegbuzie 2009). Content analysis was also used by Hider and Pymm (2008) and Järvelin and Vakkari (1990) to investigate the research methods reported in LIS journal literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Content analysis was used to identify the distribution of research strategies and techniques reported in the selected journals. Content analysis has been utilised to determine the extent to which scholars used mixed methods research (Bryman 2005;Crook et al, 2009;Greene, Caracelli & Graham 1989;Leech & Onwuegbuzie 2009). Content analysis was also used by Hider and Pymm (2008) and Järvelin and Vakkari (1990) to investigate the research methods reported in LIS journal literature.…”
Section: Methodsmentioning
confidence: 99%
“…The current research could have benefited from a mixed methods research approach as the one used by (Crook et al, 2009). Interviews of purposively selected participants might have helped the study to determine the reasons why LIS researchers in South Africa did not widely utilise MMR.…”
Section: Methodsmentioning
confidence: 99%
“…To develop a reliable and valid instrument, well-known quality controls for the development of a measurement instrument, as described by DeVellis (2003), were applied (for similar approaches, see Netemeyer, Bearden, & Sharma, 2003;Crook, Shook, Morris, & Madden, 2010; for other applications of DeVellis' method, see Govindarajan & Kopalle, 2006;Tummers, 2012). We determined what we wanted to measure on the basis of the literature on (public) innovation, generated an item pool and determined the format for measurement.…”
Section: Item Generation On the Basis The Literaturementioning
confidence: 99%
“…Unreliable measures often result conflicting findings across comparable studies because of measurement errors (Boyd et al, 2005), which may hinder the smooth advancement of knowledge. Crook et al (2010) find that though the results are satisfactory regarding internal reliability, very few of the entrepreneurship studies reported regarding inter-respondent reliability. Their results also show that number of studies depending solely on secondary data is increasing compared to those depending on primary data and on triangulation of both.…”
Section: Reliability and Validity Issuesmentioning
confidence: 87%